A study of occurrence of domestic accidents in semi-urban community - Bhanderi Dinesh; Choudhary Sushilkumar (Wolters Kluwer Medknow Publications, 2008)
Context: Domestic accidents are worldwide public health problems. The consequences of a domestic accident may prove disastrous as it may result in disability and loss of productivity. In this context, the present study was carried out to characterize the occurrence of domestic accidents in a semi-urban community. Aims: To study the incidence of domestic accident in a semi-urban community and its association with various epidemiological factors. Settings and Design: Community-based cross-sectional study of 796 households consisting of 4086 individuals residing in a semi-urban area. Materials and Methods: Complete information from 796 households consisting of 4086 individuals was collected through semi-structured, pre-tested questionnaire. Domestic accident was considered when any of these individuals had met with an accident inside the house or in the immediate surroundings of the house during the last 6 months from the date of survey. The collected data were tabulated and analyzed. Statistical Analysis Used: Simple proportions and Chi-squared test. Results: The incidence of domestic accidents was found to be 1.7%. The most common accident reported was fall. Occurrence of falls was found to be associated with age and overcrowding. Other accidents noted were burns, scalds, electrocution, injuries and accidental poisoning. Accidents were reported in significantly higher proportion in extreme age groups and in females. Higher proportion of accidents occurred during the morning and evening hours. About 10.1% were treated at home, 72.5% as outdoor patients and 17.4% as indoor patients. The mean duration of hospital stay was found to be 2 weeks. Full recovery was observed in 82.6% cases, whereas permanent disability was found in only 2.9% subjects, while 14.5% reported chronic pain after the accident. No death related to domestic accident was reported in the present study. Conclusions: Domestic accidents are more common in extreme age groups and in females. The reasons may be the higher amount of time spent at home and greater participation in daily home activities. Falls being the most frequent type of accidents, proper designing of house and adequate illumination may help in reducing their occurrence, as the majority of accidents occurred during the morning and evening hours in our study.